Bruce Bronzan 40th Birthday Party at Fresno City College Old Administration Building Courtyard - Watkins, Howard::::::::: (1987)
Bruce Bronzan blowing out 40 candles on two birthday sheet cakes Cake decorations: "Happy Over the Hill … Bruce" + "40th Birthday"